Cities, occupations and rights in this time: files, history and resistance - Lemos, Flavia Cristina Silveira [UNESP]; Galindo, Dolores; Silva, Daiane Gasparetto da; Lima, Bruno Jay Merces de (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2022)
This article aims to conduct an analysis of some urban squatters in their resistance to removal and segregation practices in cities. Think rights violations of files and contemporary struggles for occupation of space in housing policies and access to culture, transport, health and education. The insurance workers controls, articulated in various neoliberal strategies of urban management try to silence these movements and prevent revolts and political organization. Therefore, trigger repressive practices, violence and criminalization of the fights. Still, there have been constant movements and their practices of resistance in search of protecting social rights established in national and international documents and to fight for the invention of new rights.
Keywords: Occupation; city; files; history; resistences